Peningkatan Kualitas Kehidupan dengan Pelatihan Kewirausahaan Budidaya Jamur Tiram di Desa Tempuran - Sari, Reni Permata; Mariana, Erni (BAGIMU NEGERI : JURNAL PENGABDIAN KEPADA MASYARAKAT, 2019)
The need variety  of each individual insists that the people innovate and try new things. Create new activities or jobs by entrepreneurship in oyster mushroom cultivation, help citizens to use their land, provide knowledge about the cultivation of oyster mushrooms. Land use and high motivation are needed when this activity happened. Because the cultivation of oyster mushrooms does not require extensive land. Through this training, it was found that the community needed entrepreneurship training to increase their income which improving their quality of life. Improving the quality of life through oyster mushroom cultivation held in the Tempuran area, especially housewives, received a positive response. It can be a medium for mutual learning, the way to communicate in increasing insight and to change the paradigm that they can do nothing to be sure that they can do such activities and even provide healthy food for the family.